A Case Study on Annoyance Noise Caused by Metro Railway at a TOD Developed Depot. (25th April 2022) - Liu, Qiang; Kang, Zhongxu; Zhang, Hougui; Song, Ruixiang; Li, Ge
Abstract : As an importance strategy to finance the transport infrastructure investment, transit-oriented development (TOD) for railway depot is rapidly growing in China. However, railway-induced noise emerged as the leading environmental nuisance triggering one of the most common public complaints. In order to discuss the influence of railway-induced noise on the neighbourhood residents in a TOD developed depot, a special case study is provided in this study. Measurement campaigns were conducted for responding to the complaints, and noise map was calculated for finding out a noise control solution. Based on the recommendation awakening threshold value of 42 dB (A) summarized from the Night Noise Guidelines for Europe (WHO, 2009), the measurement results confirmed that the neighbourhood residents were indeed suffering from the instantaneous railway noise, and the sleep disturbance correlated indicator LAmax was more than 56 dB (A) at outside of buildings. Furthermore, calculation results indicated that the lower office buildings became mirrors which reflected the noise across over the cover structure to the higher stories of residents' buildings. At the ends, a kind of dissipative splitter muffler was proposed as a potential solution, and its performance was also simulated.